2021
DOI: 10.1038/s41388-021-01729-1
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane and coiled-coil domain family 3 (TMCC3) regulates breast cancer stem cell and AKT activation

Abstract: Cancer stem cells (CSC) play a pivotal role in cancer metastasis and resistance to therapy. Previously, we compared the phosphoproteomes of breast cancer stem cells (BCSCs) enriched subpopulation and non-BCSCs sorted from breast cancer patient-derived xenograft (PDX), and identified a function unknown protein, transmembrane and coiled-coil domain family 3 (TMCC3) to be a potential enrichment marker for BCSCs. We demonstrated greater expression of TMCC3 in BCSCs than non-BCSCs and higher expression of TMCC3 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…[ 67 ] Moreover, silencing transmembrane and coiled-coil domain family 3 (TMCC3) reduced AKT activation and inhibited the self-renewal and metastasis of breast cancer stem cells. [ 68 ] Herein, our data showed that B7-H3 overexpression elevated p-AKT and Nrf2 protein expression. Furthermore, perifosine treatment reversed the effect of B7-H3 on GSH metabolism and the stemness of GC cells.…”
Section: Discussionmentioning
confidence: 78%
“…[ 67 ] Moreover, silencing transmembrane and coiled-coil domain family 3 (TMCC3) reduced AKT activation and inhibited the self-renewal and metastasis of breast cancer stem cells. [ 68 ] Herein, our data showed that B7-H3 overexpression elevated p-AKT and Nrf2 protein expression. Furthermore, perifosine treatment reversed the effect of B7-H3 on GSH metabolism and the stemness of GC cells.…”
Section: Discussionmentioning
confidence: 78%
“…The solute carrier (SLC) and ATP-binding cassette (ABC) transporter superfamilies are critical in the processes of drug absorption, distribution, metabolism, and elimination, marking their importance in the field of pharmacology [34]. Through next-generation sequencing (NGS) RNAseq analysis, we observed significant upregulation of stemness-associated genes (TMCC3, UGT2B7, PCAT18, SOX13, REG1A) among the top differentially expressed genes (DEGs) in K562-IR cells compared to their non-resistant counterparts [35][36][37]. Notably, SLC25A48 and SLC30A8 emerged as the most upregulated SLC transporters, with fold changes (log 2 ) of 7.57 and 6.3, respectively, making them among the top 50 upregulated DEGs.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we had established three PDXs of human breast cancer, including BC0145, BC0244, and BC0350R1 in mice and identified H2K d− CD24 − CD44 + in BC0145 and ALDH + cells in BC0244 and BC0350R1 as markers for their CSCs [8,10]. Subsequently, our comparative phosphoproteomic analysis revealed greater phosphorylated YAP at Serine 61 (2.7 and 19.1 folds) and Threonine 63 (2.8 and 18.7 folds) in BCSCs than in non-BCSCs in two repeated experiments [11] (Additional file 1: Fig.…”
Section: Yap Expression In Bcscs Contributes To Enhanced Cell Prolife...mentioning
confidence: 99%